The Effectiveness of Citro Soda Solution for Relief of Epigastric Discomfort and Dyspepsia in the Intraoperative Period During Elective Cesarean Section Under Spinal Anesthesia: A Randomized Controlled Trial - Khurshid, Ayesha (Indus Journal of Bioscience Research, 2025)
Objectives: This study aimed to evaluate the effectiveness of Citro Soda solution in relieving intraoperative dyspepsia among patients undergoing elective cesarean sections (LSCS) under spinal anesthesia. Study Settings: The study was conducted in the Department of Anesthesia at Holy Family Hospital over a six-month period following approval from the institutional ethics committee. Duration of Study: Six months from 16 July 2024 to 15 January 2025. Methodology: This randomized controlled trial (RCT) included 60 patients, randomly assigned to receive either Citro Soda (n=30) or placebo (n=30) one hour prior to spinal anesthesia. Inclusion criteria comprised women aged 18–55 years undergoing elective cesarean section with subjective dyspepsia in their third trimester. Patients with chronic gastritis, gastrointestinal disease, or major comorbidities were excluded. The primary outcome was subjective relief of dyspeptic symptoms, assessed intraoperatively. Surgical duration and pain relief scores were also compared between the two groups. Results: The mean surgical duration was 62.24 minutes (±16.88) in the Citro Soda group and 60.13 minutes (±16.27) in the placebo group (p = 0.623). The mean pain relief score was 1.20 (±0.41) in the Citro Soda group compared to 1.37 (±0.49) in the placebo group (p = 0.157). Conclusion: Citro Soda did not significantly reduce intraoperative dyspepsia during cesarean section under spinal anesthesia. While it remains an effective gastric acid neutralizer, it does not appear to provide meaningful symptomatic relief.